Occupation, Dignity, and Space: The Rise of Dalit Studies - Rawat, Ramnarayan S. (History compass, 2013)
Dalit Studies has emerged as a new field of study in South Asia since the 1990s, helping to reorient scholarship's interest away from the study of untouchability as a phenomenon toward a recognition and recovery of Dalit actors. This review essay identifies three broad themes-occupation, dignity, and space, and uses them to survey the literature on Dalit society over the last hundred years. It suggests that occupation was a prominent organizing category in colonial and early post-colonial ethnographic writing that was used to catalogue and define Dalit religious traditions and socio-economic practices. Struggles for dignity and efforts to eradicate caste inequality have become central concerns in more recent writings. This essay also draws attention to a less recognized theme by focusing on the role of space, particularly the role of jati mohallas, in mediating the experience of caste and shaping Dalit political consciousness.